Recurrent biliary dissemination of colon cancer liver metastasis: a case report - Onishi, Ichiro (J Med Case Rep, 2018)
BACKGROUND: Most colorectal cancer liver metastases form nodules within the hepatic parenchyma, and hepatectomy is the only radical treatment for synchronous metastases. There is concern about intrabiliary tumor growth which may affect the surgical margin, resulting in local recurrence after hepatectomy for colorectal cancer liver metastasis; however, there has been no report of the dissemination in the bile duct after hepatectomy. Here, we report an unusual case of biliary dissemination of colorectal cancer that caused recurrent intrabiliary growth after hepatectomy, and discuss the management of intrabiliary metastasis of colorectal cancer. CASE PRESENTATION: A 69-year-old Japanese man underwent treatment for liver dysfunctions 3 years after aortic valve replacement. Computed tomography revealed an enhanced tumor within the hilar bile duct and dilatation of the left hepatic duct, typical of hilar cholangiocarcinoma. Endoscopic retrograde cholangiopancreatography revealed tumor shadow in his bile duct, and the cytology confirmed malignant cells in the bile. We performed extended left hepatectomy with bile duct resection; his postoperative course remained good without acute complications. After 3 months postoperatively, he was readmitted for subacute cholangitis and obstructive jaundice. Immediately, percutaneous transhepatic cholangiography drainage was performed, followed by cholangiography that exhibited intrabiliary tumor growth in the remnant liver. On immunohistochemical examination, tumor cells were positive for cytokeratin 20 and CDX2 but negative for cytokeratin 7. Then, computed tomography revealed an enhanced tumor-like lesion at the descending colon. After 3 months, left hemicolectomy was performed. Meanwhile, the percutaneous transhepatic cholangiography drainage fluid turned bloody, which was considered to be bleeding from a residual bile duct tumor. Accordingly, radiotherapy was initiated to prevent tumor bleeding around the hilar bile duct, but, unfortunately, the effects were short-lived, and cholangitis rebooted after 1 month leading to our patient’s death due to septic liver failure. Autopsy revealed a remnant tumor in the bile duct, but no noticeable nodular metastasis was observed, except for a single small metastasis in the lower lobe of the left lung. CONCLUSIONS: The intrabiliary growth of metastatic colorectal cancer mimics cholangiocarcinoma occasionally. To date, as the effect of chemotherapy or radiotherapy remains uncertain, the complete resection of a bile duct tumor is the only method which could result in a better prognosis.